2017
DOI: 10.1111/pops.12470
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Loch Ness Monster: Left-Wing Authoritarianism in the United States

Abstract: Although past research suggests authoritarianism may be a uniquely right-wing phenomenon, the present two studies tested the hypothesis that authoritarianism exists in both right-wing and left-wing contexts in essentially equal degrees. Across two studies, university (n 5 475) and Mechanical Turk (n 5 298) participants completed either the RWA (right-wing authoritarianism) scale or a newly developed (and parallel) LWA (left-wing authoritarianism) scale. Participants further completed measurements of ideology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
204
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(216 citation statements)
references
References 40 publications
9
204
1
2
Order By: Relevance
“…Other emerging findings in the cross-sectional "Trump" literature suggest that denial of racism and sexist attitudes are associated with Trump support (Schaffner et al, 2018); however, scale construction is often self-evidently biased in favor of liberal worldviews (Reyna, 2018). The denial of racism and sexism scales in Schaffner et al (2018) suffer from the same ideological bias as modern racism scales (Carney & Enos, 2018;Chambers, Schlenker, & Collisson, 2013;Sniderman & Tetlock, 1986) and authoritarianism scales (Conway, Houck, Gornick, & Repke, 2017;Malka, Lelkes, & Holzer, 2018;Vallerga, 2010), which because of including conservative political content within scale items, by definition must be associated with support for conservative candidates. To claim that agreement with "Racial problems in the U.S. are rare, isolated situations" acts as an indication of racism rests on the assumption that racial problems are ubiquitous and pervasive, which data easily contradicts.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…Other emerging findings in the cross-sectional "Trump" literature suggest that denial of racism and sexist attitudes are associated with Trump support (Schaffner et al, 2018); however, scale construction is often self-evidently biased in favor of liberal worldviews (Reyna, 2018). The denial of racism and sexism scales in Schaffner et al (2018) suffer from the same ideological bias as modern racism scales (Carney & Enos, 2018;Chambers, Schlenker, & Collisson, 2013;Sniderman & Tetlock, 1986) and authoritarianism scales (Conway, Houck, Gornick, & Repke, 2017;Malka, Lelkes, & Holzer, 2018;Vallerga, 2010), which because of including conservative political content within scale items, by definition must be associated with support for conservative candidates. To claim that agreement with "Racial problems in the U.S. are rare, isolated situations" acts as an indication of racism rests on the assumption that racial problems are ubiquitous and pervasive, which data easily contradicts.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…They show that the relationship between fear and right-wing orientation was positive, rather than negative (r [22,777] = 0.1038, p <.001), and so was the relationship between fear and authoritarianism (r [24,325] = 0.1748, p <.001), although these relationships were not reported in the original article. And-for those who remain skeptical, despite decades of evidence, about the existence of an "elective affinity" between authoritarianism and right-wing orientation (e.g., Conway, Houck, Gornick, & Repke, 2018;Ditto et al, 2019)-it is worth pointing out that these two variables were quite strongly correlated in the context of this very large, nationally representative survey in France (r [22,777] = 0.2284, p <.001). In addition, fear was positively correlated with rightist political orientation (or negatively correlated with leftist orientation), measured in terms of ideological self-placement (r [22,777] = 0.1038, p <.001).…”
mentioning
confidence: 97%
“…While some authors question the existence of leftwing authoritarianism (Altemeyer, 1996(Altemeyer, , 1998Jost, Blount, et al, 2003;Jost, Glaser, et al, 2003), others show that authoritarian tendencies can be observed among extreme left-wing activists but not the general public (Van Hiel, Duriez, & Kossowska, 2006), while still others argue that using proper measurements authoritarianism exists to similar degrees on both sides of the political spectrum (Conway, Houck, Gornick, & Repke, 2017). While some authors question the existence of leftwing authoritarianism (Altemeyer, 1996(Altemeyer, , 1998Jost, Blount, et al, 2003;Jost, Glaser, et al, 2003), others show that authoritarian tendencies can be observed among extreme left-wing activists but not the general public (Van Hiel, Duriez, & Kossowska, 2006), while still others argue that using proper measurements authoritarianism exists to similar degrees on both sides of the political spectrum (Conway, Houck, Gornick, & Repke, 2017).…”
mentioning
confidence: 99%
“…The present findings are also relevant for the debate about whether authoritarianism is a right-wing phenomenon or can be found on the political left as well. While some authors question the existence of leftwing authoritarianism (Altemeyer, 1996(Altemeyer, , 1998Jost, Blount, et al, 2003;Jost, Glaser, et al, 2003), others show that authoritarian tendencies can be observed among extreme left-wing activists but not the general public (Van Hiel, Duriez, & Kossowska, 2006), while still others argue that using proper measurements authoritarianism exists to similar degrees on both sides of the political spectrum (Conway, Houck, Gornick, & Repke, 2017). Going beyond measurement issues, the present findings suggest that political sophistication plays an important role in whether authoritarian tendencies are associated with a consistent pattern of conservative political attitudes or with traditionally liberal viewpoints as well.…”
mentioning
confidence: 99%